The Remainder Theorem is an approach to Euclidean polynomial division. According to this theorem, dividing a polynomial P(x) by a factor (x - a), which is not an element of the polynomial, yields a smaller polynomial and a remainder. Here you can check the answer for Find Remainder of 2x^3-x^2+10x by x+2 using Remainder Theorem.
Ex: x^2+2x+1,x+1 (or) x^2-1,x-1 (or) x^3-1,x+1
Given values are
f(x) = 2x^3-x^2+10x
x = -2.
Given Polynomial is 2x^3-x^2+10x .
= (x)+(2.x^2 - x + 10)
By putting x = (-2) we can rewrite it as
= ((-2))+(2.(-2)^2 - (-2) + 10)
The remainder of given polynomial is -40.
1. What is the remainder of 2x^3-x^2+10x by x+2?
The Remainder of 2x^3-x^2+10x divided by x+2 is -40.
2. How to Find Remainder of 2x^3-x^2+10x by x+2 using Remainder Theorem?
Consider x+2 = 0 so that x = -2.
Substitute x = -2 in expression 2x^3-x^2+10x to get the remiander
Thus, 2x^3-x^2+10x divided by x+2 remainder is -40.
3. Where can I obtain detailed solution steps for Remainder Theorem of 2x^3-x^2+10x?
The detailed steps for the Remainder Theorem of 2x^3-x^2+10x are compiled exclusively on our output page.